PENGARUH PEMBERIAN KUNYIT DAN MADU TERHADAP PENURUNAN NYERI HAID (DYSMENORRHAE) PADA REMAJA PUTRI DI KECAMATAN MEDAN AMPLAS KOTA MEDAN TAHUN 2022 - Riristio Panggabean; Putri Ayu Yessy Ariescha; Vivi Elvira (JURNAL ILMIAH DHDT - KEBIDANAN, 2022)
Abstract Dysmenorrhea is lower abdominal pain during menstruation that can interfere with daily activities. Pain arises due to increased levels of prostaglandins. Prostaglandins have an effect that can increase the contractility of the uterine muscle and prostaglandins also have a vasoconstrictive effect that can cause ischemia in the uterine muscle and can cause pain. Research on the effect of giving turmeric and honey on the reduction of menstrual pain (dysmenorrhea) in adolescent girls was conducted in the Medan Amplas sub-district. A decoction of turmeric and honey is given 3 times a day as much as 150 mL for 2 days. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after giving turmeric and honey. Data were collected using Questionnaires and Observation sheets. The number of samples in this study was 15 young women. The sampling technique used was accidental sampling. Analysis of the data used is the Paired T-test. The results of this study showed that the intensity of pain before being given boiled honey turmeric water which had a moderate pain scale was 10 people (66%). The intensity of pain after being given boiled honey turmeric water which has a mild scale of 12 people (80%), namely with a value of p = 0.000 (p <0.05), which means that there is an effect of giving honey turmeric water decoction to decrease the intensity of menstrual pain in Teenage girl.